Expression Regulation and Function of T-Bet in NK Cells - Huang, Chen; Bi, Jiacheng (Frontiers in Immunology, 2021)
Natural killer (NK) cells are cytotoxic innate lymphocytes that play an important role in immune surveillance. The development, maturation and effector functions of NK cells are orchestrated by the T-box transcription factor T-bet, whose expression is induced by cytokines such as IFN-, IL-12, IL-15 and IL-21 through the respective cytokine receptors and downstream JAK/STATs or PI3K-AKT-mTORC1 signaling pathways. In this review, we aim to discuss the expression and regulation of T-bet in NK cells, and the role of T-bet in mouse NK cell development, maturation, and function, as well as the role of T-bet in acute, chronic infection, inflammation, autoimmune diseases and tumors.